Internalization of Strengthening Character Education through Scouting Extracurricular Activities for Students SMK - Arief Eko Setiawan; Marsono Marsono; Yoto Yoto (Budapest International Research and Critics University, 2021)
Currently the Indonesian nation is experiencing moral degradation. This problem actually occurs in many teenagers as one of the impacts of the era of globalization and technological developments. The industrial era 4.0 and technological developments can have positive and negative impacts on almost all levels of society. One of the negative impacts that arise is the decline in the character of the younger generation. Researchers are interested in conducting further research on the internalization of KDP through extracurricular activities, especially Scout extracurricular activities in two schools, namely SMKN I Kademangan and SMK PGRI Wlingi, Blitar Regency. This research uses a qualitative approach with a case study research design. Data collection techniques with free and open interviews, documentation studies, and observation. The informants of this study were 50 students who became members of the scouts and as representatives of respondents. Based on the results of the analysis conducted on the research data, it is known that several forms of internalization of the values of strengthening character education contained in the Scout extracurricular program can be seen from the values of religious character, nationalist character, integrity character, independent character, and mutual cooperation character. In addition to internalizing these characters, scout extracurricular activities also include self-development efforts that foster students' organizational and entrepreneurial skills.